Impact of Financial Repression on FDI in Iran - Majdi, Saman (Eastern Mediterranean University (EMU), 2011)
This thesis has investigated the impact of financial repression on FDI in Iran from 1965 to 2005 through Johansen Cointegration tests. The thesis has empirically investigated the determinants of FDI in Iran while testing for the impact of financial repression on FDI in the country. Overall, the findings obtained in this thesis for the conventional determinants of FDI are mostly in line with the existing theories in the literature. The results suggested that that capital, market size, trade openness, and Research and Development (Technology) have a positive statistically significant impact on FDI. On the other hand, inflation and financial repression are significant with a negative coefficient which means that these two variables have a negative impact on FDI. An interesting result of the thesis is that human capital and labor are not significant in the cointegration models. This has shown that the status of the human resources in Iran is not instrumental in attracting direct investment from overseas, which can be attributed to low productivity of the labor in Iran.
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2011. Supervisor: Assist. Prof. Dr. Mete Feridun.
Keywords: Business Administration; Iran - Economic Conditions and Development; Economic Growth - Foreign Direct Investment (FDI) - Iranian Economy; Investments, Foreign; Cointegration - Financial Repression